The role and functions of a family in Polish economists’ writings at the turn of the XIXth century - Bołdyrew, Aneta (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The changes in the social and economic life in Poland at the turn of the XIXth century changed and influenced also the functioning of the family, marked new norms, influenced the modification of the values connected with family life and also determined the transformations of the functions and tasks fulfilled by the family. Still, the role of the family which functioned according to the law, was to fulfill numerous tasks serving the family itself and the whole of society. A family was prescribed not only intrinsic values but also utilitarian values which were to serve the country and society. At the turn of the XIXth century the family became the object of interest to intellectuals, publicists and social activists which resulted in a number of normative, descriptive and theoretical publications.
Keywords: family; economists; Zofia Daszyńska-Golińska; Ludwik Krzywicki